pradeepss wrote:
Shameek,
You have the correct expression for 1.
I read in
MGMAT guides as follow:
if square of Y = 1, then Y = + or - 1. GMAT approach is, if Y = 1 then square of Y = 1 and if Y = -1 the square if Y is still 1.
Hope that helps.
First of all I would like to know where does square of Y comes into picture in this question. If you open the 1st statement's expression you get
\(X*Y + (\frac{Y}{2}) = 1\)
which will be \(\frac{Y}{2} + \frac{Y}{2} = 1\)
i.e. Y = 1 - Hence Sufficient
For the second statement :-
Y*(2X-1) = 2X - Y
2XY - Y = 2X - Y
i.e. 2XY - 2X = 0
i.e. 2X(Y-1) = 0
either X = 0 or Y = 1
Given that \(X = \frac{1}{2}\) we are left with Y = 1
And yes \(\sqrt{Y^2} = |Y|\); and therefore 2 solutions for Y.
But why are you concerned with it for this question? I don't get that.
Also according to me the answer should be "D" not "B".